Pedagogia Universitária e Redes de Pesquisa: laços em busca da consolidação de uma universidade pública em Mato Grosso/Brasil - de Nez , Egeslaine; Pessoa Bitencourt , Loriége; Diefenthaeler Krahe , Elizabeth; Estela Dal Pai Franco , Maria (Revista Vozes dos Vales: Publicações Acadêmicas, 2015)
This article explores the dialogue between two investigations developed within the research line "University: theory and practice" of the Postgraduate Program at the Federal University of Rio Grande do Sul, which has the same state public university as its investigative locus. The methodological procedures used in the investigations were: bibliographic research, documentary research, field research, and content analysis with a qualitative analytical approach. The scientific relevance of the studies is evident because the region served by the analyzed university (Central-West) is emerging in the constitution of Postgraduate studies in Brazil, due to repressed demand and because University Pedagogy is not the subject of discussion and implementation as an institutional policy. The solutions indicated in the investigations suggest the expansion of research groups and the composition of research networks with a view to consolidating Postgraduate studies and collaborative work that relates school-university, with their respective subjects, in favor of excellent teacher training. Finally, it is possible to consider that the public institution analyzed has the potential for the development of quality University Pedagogy, since possibilities and resources available within it are perceptible.